2006
DOI: 10.1158/1078-0432.ccr-06-1164
|View full text |Cite
|
Sign up to set email alerts
|

FGFR1 Emerges as a Potential Therapeutic Target for Lobular Breast Carcinomas

Abstract: Purpose: Classic lobular carcinomas (CLC) account for 10% to 15% of all breast cancers. At the genetic level, CLCs show recurrent physical loss of chromosome16q coupled with the lack of E-cadherin (CDH1 gene) expression. However, little is known about the putative therapeutic targets for these tumors. The aim of this study was to characterize CLCs at the molecular genetic level and identify putative therapeutic targets. Experimental Design: We subjected 13 cases of CLC to a comprehensive molecular analysis inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
256
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 258 publications
(271 citation statements)
references
References 44 publications
9
256
0
3
Order By: Relevance
“…We [31,42,55] and others [39,43] have previously demonstrated that genes significantly overexpressed when amplified are likely amplicon drivers, as the expression of these genes is required for the survival of cells harbouring amplification of their genomic region. Our integrated analysis has not only identified genes previously shown to be potential drivers of amplicons 8p11.2 (FGFR1), 8q24 (MYC), 11q13 (CTTN, FADD), 17q12 (ERBB2) and 20q13 (AURKA), but also identified a list of 269 that should be investigated as potential therapeutic targets in the amplicons on chromosomes 1q, 3q, 6p, 8q, 13q, 14q, 17q, 19q and 20q (Table 4; Supplementary Table S6).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We [31,42,55] and others [39,43] have previously demonstrated that genes significantly overexpressed when amplified are likely amplicon drivers, as the expression of these genes is required for the survival of cells harbouring amplification of their genomic region. Our integrated analysis has not only identified genes previously shown to be potential drivers of amplicons 8p11.2 (FGFR1), 8q24 (MYC), 11q13 (CTTN, FADD), 17q12 (ERBB2) and 20q13 (AURKA), but also identified a list of 269 that should be investigated as potential therapeutic targets in the amplicons on chromosomes 1q, 3q, 6p, 8q, 13q, 14q, 17q, 19q and 20q (Table 4; Supplementary Table S6).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated that expression of genes consistently overexpressed when amplified may be required for the survival of cells harbouring amplification of their genetic loci [31,39,42,43]. To identify the likeliest drivers of the amplicons 8p11.2-p12, 8q24, 11q13.3, 17q12-q21 and 20q13.3, we first retrieved the genes mapping to these amplicons, performed a Pearson's correlation to determine those whose expression correlate with copy number and then identified all genes that were overexpressed when amplified within each region using a Wilcoxon sign rank test (Fig.…”
Section: Identification Of Likeliest Amplicon Drivers Of Recurrent Ammentioning
confidence: 99%
“…8p12-p11 and 11q12-q13, loss of 11q14-qter, gain of 12q23-q24, loss of 15q21, loss of 16q22, gain of 19p13, gain of 20q11-q13, and several other distinct alterations [9,10]. The total number of chromosomal arms with genomic imbalances in primary ILBC ranges from 3 to 15 [10].…”
Section: Epithelial Origin and Lack Of E-cadherin Expression In Iph-926mentioning
confidence: 99%
“…Profiling approaches focusing on genomic imbalances established that nearly all ILBCs harbour a loss of 16q22, the locus of CDH1 [9]. This alteration is frequently accompanied A CDH1-null cell line from lobular breast cancer 621 by gain of 1q, loss of 8p23-p22, concomitant gains of 8p12-p11 and 11q12-q13, and loss of 11q14-qter [9,10]. In the clinics, ILBCs frequently metastasize to the peritoneum and abdominal organs [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation